Mobile Device Security Evaluation using Reverse TCP Method - Riadi, Imam; Sunardi; Aprilliansyah, Deco (Universitas Muhammadiyah Malang, 2022)
Security evaluation on Android devices is critical so that users of the operating system are protected from malware attacks such as remote access trojans that can steal users' credential data. Remote access trojan (RAT) attacks can be anticipated by detecting vulnerabilities in applications and systems. This study simulates a remote access trojan attack by exploiting it until the Attacker gains full access to the victim's device. The episode is carried out with several steps: creating a payload, installing applications to the victim's device, connecting listeners, and performing exploits to retrieve important information on the victim's device. Test material using Android 12, problems occurred when trying to install the application because a harmful warning will appear from Play Protect due to not using the latest version of privacy protection which causes the application to be indicated as malware and the like. On Android 11, the application injected with the backdoor was successfully installed on the device and successfully accessed by the attacker. Attackers also get vital information, including system information, contacts, call logs, messages, and full access to the victim's device system directory. Based on this research, it is expected that Android device users constantly update the Android version on the device they are using.